Transport phenomena of fire-induced smoke flow in a semi-open vertical shaft. Issue 11 (17th October 2018) - Li, Decheng; Zhou, Tiannian; Liu, Zegong; Wang, Jian
Abstract : Purpose: The purpose of this study is to investigate the transport phenomena of smoke flow in a semi-open vertical shaft. Design/methodology/approach: The large eddy simulation (LES) method was used to model the movement of fire-induced thermal flow in a full-scale vertical shaft. With this model, different fire locations and heat release rates (HRRs) were considered simultaneously. Findings: It was determined that the burning intensity of the fire is enhanced when the fire attaches to the sidewall, resulting in a larger continuous flame region in the compartment and higher temperatures of the spill plume in the shaft compared to a center fire. In the initial stage of the fire with a small HRR, the buoyancy-driven spill plumes incline toward the side of the shaft opposite the window. Meanwhile, the thermal plumes are also directed away from the center of the shaft by the entrained airflow, but the inclination diminishes as HRR increases. This is because a greater HRR produces higher temperatures, resulting in a stronger buoyancy to drive smoke movement evenly in the shaft. In addition, a dimensionless equation was proposed to predict the rise-time of the smoke plume front in the shaft. Research limitations/implications: The results need to be verified with experiments. Practical implications: The results could be applied for design and assessment of semi-open shafts. Originality/value: This study shows the transport phenomena of smoke flow in a vertical shaft with one open side.